2002
DOI: 10.1111/j.1939-1676.2002.tb01259.x
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic and Radiographic Changes Associated with Systemic Hypertension in Cats

Abstract: The purpose of this study was to assess the effects of systemic hypertension (SHT) on echocardiographic and radiographic cardiovascular variables in affected cats compared with healthy geriatric cats. Secondary objectives were to determine whether there were any relationships between these findings and age or systolic blood pressure (SBP). Fifteen healthy cats (Ͼ8 years of age with normal SBP) and 15 hypertensive cats (SBP Ͼ 180 mm Hg) were studied. Each cat was evaluated for standard echocardiographic paramet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 24 publications
(29 reference statements)
3
22
1
Order By: Relevance
“…[21][22][23][24] The present study is the first to present data from a feline referral population in Italy. HCM is the most common CM diagnosed at our institution (53% of the population included), followed by secondary CM (32% of the population included) and RCM (15%).…”
Section: Discussionmentioning
confidence: 82%
“…[21][22][23][24] The present study is the first to present data from a feline referral population in Italy. HCM is the most common CM diagnosed at our institution (53% of the population included), followed by secondary CM (32% of the population included) and RCM (15%).…”
Section: Discussionmentioning
confidence: 82%
“…As in humans [14][15][16], left myocardial hypertrophy is the most frequent result of feline SHT [8][9][10][11][12]. The echocardiographic study conducted by Snyder et al, performed in 2001 on 19 hypertensive cats [8], demonstrated for the first time that these cats had significantly thicker septal and left ventricular free walls than normal cats.…”
Section: Feline Systemic Arterial Hypertension Left Ventricular Remodmentioning
confidence: 92%
“…The A3 and A4 diameters along with the A4/A1 and A3/A1 ratios were found to be significantly higher in hypertensive cats compared to a healthy feline control group. They were also positively correlated with the systolic arterial pressure value [9]. • Rarely, the aortic dilation secondary to SHT may lead to functional aortic regurgitation due to valvular annulus dilation (Figure 16-6).…”
Section: Other Cardiovascular Changes Observed In Conventional Echo Dmentioning
confidence: 93%
See 2 more Smart Citations